The Joy of Science - Lockshin, Richard A. (Springer, 2007)
Scientists have great passion. What could be more exhilarating than to go to work every day feeling as if you were once again a nine-year-old called up to he stage to help the magician with his trick? To be a researcher is to always be in the position of having the chance to see how the trick works. No wonder that many researchers feel that each new day is the most exciting day to be a scientist. It therefore is not surprising that scientists have such trouble communicating with non-scientists. It is difficult for the scientist to understand a life not focused on the desire to understand. But the differences are not that. Everyone wants to understand; that is one of the factors that make us human. The difference is more that scientists limit their definition of comprehension to specific rules of logic and evidence. These rules apply and are used in everyday life, but often with less rigor or restrictions on evidence. The structure of this book is therefore tripartite. On the first level, we wish to demonstrate that, far from being arcane or inaccessible, the scientific approach is simply a variant of normal, common experience and judgment, easily accessible to any educated person. The second goal is to explain the structure of scientific thinking, which we will describe as the requirement for evidence, logic, and falsification (experimental testing). The third goal is to illustrate the scientific method by looking at the story of the development of the idea of evolution. Evolution is a branch of scientific inquiry that is distinguished by its minimal level of laboratory experimentation, as least in its early period. Nevertheless, the story of evolution seems for several reasons to be an excellent choice to examine the nature of scientific inquiry. First, it is, almost without doubt, the most important idea of the 19th and 20th centuries. Second, it is often misunderstood. Third, understanding the story does not require an extensive technical background. Finally, it is very multidisciplinary.
An Examination of How Scientists Ask and Answer Questions Using the Story of Evolution as a Paradigm